2018
DOI: 10.2135/cropsci2018.02.0106
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Resistance to Bean Weevil in Common Bean

Abstract: The common bean weevil (Acanthoscelides obtectus [Say]) is an important postharvest pest of common bean (Phaseolus vulgaris L.) seed. To expand the current knowledge of resistance to A. obtectus, a quantitative trait loci (QTL) analysis was conducted using a common bean population of 210 F4:5 recombinant inbred lines derived from a cross of Solwezi, a susceptible bean landrace from Zambia, with breeding line AO‐1012‐29‐3‐3A that possesses resistance to A. obtectus. This population was genotyped with 5398 singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…A mapping population of 150 F 4:8 RILs derived from a cross between two Andean parents Solwezi and AO‐1012‐29‐3‐3A (AO) was studied. This mapping population was derived using single seed descent method (Kamfwa, Beaver, Cichy, & Kelly, 2018; Kamfwa, Cichy, & Kelly, 2019). Solwezi is a Zambian landrace, with a type IV growth habit (climber) and red‐mottled seed type, and is widely grown in Zambia.…”
Section: Methodsmentioning
confidence: 99%
“…A mapping population of 150 F 4:8 RILs derived from a cross between two Andean parents Solwezi and AO‐1012‐29‐3‐3A (AO) was studied. This mapping population was derived using single seed descent method (Kamfwa, Beaver, Cichy, & Kelly, 2018; Kamfwa, Cichy, & Kelly, 2019). Solwezi is a Zambian landrace, with a type IV growth habit (climber) and red‐mottled seed type, and is widely grown in Zambia.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding thrips resistance (Thrips palmi Karny), only a QTL named as Tpr6.1 located on Lg b06 was determined by Frei et al [114]. Concerning the bean weevil (Acanthoscelides obtectus [Say]) which is a crucial postharvest pest of common bean seed Kamfwa et al [115], discovered three QTLs on chromosomes Pv04 and on Pv06. In addition to these QTLs examples related to biotic stress factors, several QTL studies were also released about abiotic stress factors.…”
Section: Common Bean Breeding For Biotic and Abiotic Stressesmentioning
confidence: 99%
“…The low frequency of F 4 lines with high levels of resistance to weevils suggested that the complex APA locus is not the only factor associated with resistance to the common bean weevil. This information was confirmed by Kamfwa et al (2018) who identified three QTL for resistance to A. obtectus on Pv04 and on Pv06. One of the QTL on Pv04 was previously reported as the APA resistance locus while the other two QTL were new.…”
Section: Leafhoppersmentioning
confidence: 69%